Preliminary results of reduced myocardial blood flow in the subacute phase after radiation therapy for thoracic esophageal cancer: A quantitative analysis with stress dynamic myocardial computed tomography perfusion imaging. (December 2022) - Takada, Akinori; Ichikawa, Yasutaka; Nakamura, Satoshi; Toyomasu, Yutaka; Kawamura, Tomoko; Nanpei, Yui; Mase, Takamitsu; Omori, Kazuki; Mizuno, Toshiro; Kitagawa, Kakuya; Ishida, Masaki; Ii, Noriko; et al.
Highlights: Radiation for esophageal cancer results in myocardial blood flow (MBF) disturbance. The quantitative relationship between radiation dose and MBF could be evaluated. MBF can be significantly reduced in myocardial segments received ≥ 20 Gy. The reduced MBF was observed in the subacute phase after radiotherapy. Abstract: Background and purpose: Late adverse cardiac events after radiation therapy (RT) for thoracic malignancies are known, but the underlying mechanisms are poorly understood. This study aimed to determine the radiation dose that can cause MBF alterations in the subacute phase after RT for thoracic esophageal cancer using stress dynamic myocardial computed tomography perfusion imaging (CTP). Materials and methods: Twenty-five patients with esophageal cancer scheduled for RT were prospectively enrolled. The quantitative analysis of MBF by CTP was performed before and 3 months after RT. The mean radiation dose and hyperemic MBF in 15 segments of the left ventricular (LV) myocardium were determined. ΔMBF was calculated in each segment as MBFafter RT – MBFbeforeRT. The myocardial segments were classified into the following 5 groups according to the mean radiation dose: group A, <10 Gy; B1, 10–15 Gy; B2, 15–20 Gy; C, 20–30 Gy; and D, >30 Gy. Results: The final cohort included 22 patients who completed pre- and post-RT CTP. A one-way analysis of variance revealed a significant difference (p=0.005) in ΔMBF among the five groups of LV segments classified by the mean radiation dose. ΔMBF was significantly lower in group C (-7.7 ± 28.9 mL/min/100 g, p=0.020) and group D (-8.4 ± 34.8 mL/min/100 g, p=0.004) in comparison to ΔMBF in group A (4.9 ± 26.1 mL/min/100 g). Conclusions: This study using CTP early after RT demonstrated a significant reduction of the MBF in the LV segments with ≥20 Gy of radiation. The results might provide important insights into preventing radiotherapy-induced cardiac events.